Are Banks Engines of Export? Financial Structures and Export Dynamics - Minetti, Raoul; Mulabdic, Alen; Ruta, Michele; Zhu, Susan (World Bank, Washington, DC, 2018)
This paper studies the impact of financial structures on the dynamics of the export sector using rich data from over 60 countries. The results reveal that bank-oriented financial systems boost the size of the export sector more than market-oriented financial systems. However, especially in middle- and low-income countries, this effect mostly stems from banks slowing down exporters' exit rather than promoting firms' entry into export. The reduced exit from the export sector appears to reflect domestic banks' tendency to evergreen loans to exporters ("soft budget constraint") more than banks' buffering role in difficult times. Foreign banks mitigate this effect and enhance the dynamism of the export sector.